Content-Form Relationship of Environmental Education in the Reference Curriculum in the State of Mato Grosso do Sul: Analysis based on Historical-Critical Pedagogy - Cruz Zucchini, Lilian Giacomini; Campos, Luciana Maria Lunardi [UNESP] (Investigacoes em Ensino de Ciencias (IENCI), 2023)
This study aimed to analyze, in the light of historical-critical pedagogy (PHC), environmental education (EE) in the reference curriculum in the state of Mato Grosso do Sul (CRMS). More specifically, we investigated where and how it is inserted, mainly its relationship with the curriculum contents. Based on Historical and Dialectical Materialism as a theoretical and methodological reference, this was an exploratory study, whose search for information was carried out in the document under study. Analyses were carried out using a “synthesis category”, the content-form relationship, with which it was possible to empirically start to, through abstractions, critically understand EE in the CRMS. Among the results, dissociation between content and form found in the curriculum implies in the misunderstanding, by students and teachers, of the socio-environmental crisis as a synthesis of multiple determinations originating from the capitalist mode of production. As a result, space is opened for an understanding of EE as Education for Sustainable Development (ESD), an expression of neoliberal ideology, environmentalism of results, contemporary pragmatism and market ecologism.
A RELAÇÃO CONTEúDO-FORMA DA EDUCAÇÃO AMBIENTAL NO CURRÍCULO DE REFERÊNCIA DE MATO GROSSO SUL: ANÁLISE A PARTIR DA PEDAGOGIA HISTÓRICO-CRÍTICA
Keywords: Curriculum; Curriculum content; Environmental Education; Historical-Critical Pedagogy; Neoliberalism